EXPERIMENTS IN SPORTS REGULATION - Degtyarev, M.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a theoretical basis for a regulatory experiment theory in application to the sports sector. Methods and structure of the study. We used, for the purposes of the study, a set of standard analytical and generalization methods as a basic toolkit; comparative analysis of some legal and regulatory frameworks; formal legal theory and practice studies (to process the relevant regulatory and empirical input data); and a synthesizing method to design our own sports sector governmental regulatory framework concept. We analyzed the sports sector governmental regulatory framework of the following 30 nations: Australia, Austria, Argentina, Belarus, Brazil, Vietnam, Germany, Greece, Denmark, Iceland, Spain, Italy, Kazakhstan, Canada, China, Netherlands, Norway, UAE, Poland, Portugal, Russia, USA, Ukraine, Uruguay, Finland, France, Switzerland, Sweden, South Korea and Japan. Results and conclusion. It is only natural for a sports sector nowadays to demonstrate a high commitment for research, ambitious experiments and competitions – that need to be facilitated by a modern legal and regulatory framework highly sensitive to the dynamically changing conditions, environments and interests of the key actors. This is the reason why the sports sector should be advanced with contributions from the relevant efficient regulatory experiment technologies – all the more that the regulatory experiment history is several centuries old.